2007
DOI: 10.1007/s10620-006-9176-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variation of Intraepithelial Lymphocytes Subsets in Normal Human Duodenal Mucosa

Abstract: The enumeration of intestinal intraepithelial lymphocytes (IELs), and the phenotyping of CD3+CD 103+ (TcRalphabeta, TcRgammadelta) and CD3-CD103+ IEL subsets constitute useful diagnostic tools for the correct interpretation of the mucosal histology of duodenal/jejunal biopsies in many pathological conditions of the small intestine, particularly celiac disease (CD). This work evaluates the ranges of duodenal IEL counts by flow cytometry in healthy mucosa from pediatric and adult controls, establishing normal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
3
18
0
2
Order By: Relevance
“…As previously reported [21], we also found that non-CD children harbor more CD3-and NK IEL than control adults. Notwithstanding, deviations from respective control groups were exactly the same in pediatric and adult CD patients.…”
Section: Discussionsupporting
confidence: 91%
“…As previously reported [21], we also found that non-CD children harbor more CD3-and NK IEL than control adults. Notwithstanding, deviations from respective control groups were exactly the same in pediatric and adult CD patients.…”
Section: Discussionsupporting
confidence: 91%
“…(45) In older children and adults, TCR γδ T-cells represent 1% to 5% of circulating T-cells but approximately 10% to 20% of IELs in the small intestine. (46) In contrast, we detected a much higher proportion (40% to 50%) of TCR γδ T-cells within the ileum IEL in the first 6 postnatal months (personal communication, J. Weitkamp, June 2011). Although the precise role of TCR γδ T-cells is not yet clearly defined, they appear to be critical for the maintenance of epithelial integrity through antibacterial defense, TJ preservation, recognition of epithelial stress, regulation of inflammatory responses, and epithelial growth factor production.…”
Section: Cellular Innate Immune Responsementioning
confidence: 82%
“…Compared with native intestine controls, graft epithelium had fewer CD3 þ CD8 þ lymphocytes and a more prominent CD103 þ CD3 -population (CD3 -IELs). The proportion of CD3 -IELs has been reported to increase with age (26). This makes the augmentation of CD103 þ CD3 -cells in recipients more pronounced, as these subjects were significantly younger than the controls.…”
Section: Discussionmentioning
confidence: 98%